ANALISIS PERATAAN PENGHASILAN (INCOME SMOOTHING): FAKTOR-FAKTOR YANG MEMPENGARUHI DAN KAITANNYA DENGAN KINERJA SAHAM PERUSAHAAN PUBLIK DI INDONESIA - Susi Dwimulyani; Yoga Abraham (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2006)
This research is designed to eximine the income smoothing in Indonesia. Income smoothing can be defined as a tools used by management to diminish the variability of fluctuated reporting income by manipulation artificial (accounting) and real (transactional) variables (Salno and Baridwan, 2000). Investigated issues in this researchwere factors influencing income smoothing such as size, net profit margin, winner/losser stocks, and the linkage between income smoothing and the performance (return) of stocks in Indonesian Public Company.Research samples were selected using purposive (judgement) sampling method among listed company in Jakarta Stocks Exchange (JSX) and seventy companies could meet as research sample. Afterwards this samples clasified into smoother and non smoother using Eckel's model (1981). The result showed there ware income smoothing practiced by companies listed in JSX. For data analysis, this research used commonstatistics such as descriptive statistic, one sample Kolmogorov Smirnov test, Mann Whitney Test, t-test, and simple liniear regression.Before hypothesis test, normality data test using one sample Kolmogorov Smirnov test and Mann-Whitney test were used to determine whether the data were normal or not. The test concluded that data weren't normally distributed because significant level smaller than 0,05. The first, second, and third hypothesis were tested separately usingsimple liniear regression to examine whether size, net profit margin, and winner/losser stocks influenced income smoothing. The result of these three hypothesis were refused because the significant level bigger than 0,05. The fourth hypothesis examined size, net profit margin, and winner/losser stocks influenced together income smoothing. The resultof this hypothesis was refused because the significant level bigger than 0,05. The fifth hypothesis examined whether return of stocks were diferrence between smoother and non smoother. This hypothesis was tested with Mann-Whitney test and the conclution was no return diferrence between smoother and non smoother because significant level bigger than 0,05.